RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDE OF PREGNANT WOMEN ABOUT THE FIRST 1000 DAYS OF LIFE AND STUNTING PREVENTION (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2025)
Background: Stunting is a condition in which a child experiences growth and development disorders due to lack of nutritional intake for a long time. The First 1000 Days of a baby's life can prevent stunting Mothers' perspectives and understanding of the first 1000 days are crucial in preventing stunting.Objective : to ascertain the relationship In Suka Damai Village, Hinai District, Langkat Regency, a pregnant mother's knowledge and attitude toward the first 1000 days of life with stunting prevention.Method : analytical survey research with design study Which used is cross sectional . Population study This is Mother pregnant who checks Her pregnancy . The population is 40 people and with technique total sampling . Instrument use questionnaire and techniques data analysis using analysis chi square .Results : Most of the twenty-three individuals knew enough. (32.5%), the majority is positive (26, or 65.0%), the minority is good (four, or 10.0%), and the attitude is negative (only 14, or 35.0%). In Peaceful Village, Hinai District, there is a correlation between pregnant women's attitudes throughout the first 1000 days of life and their ability to prevent stunting (p-value = 0.000; p